Hydroxy- and Amino-Phosphonates and -Bisphosphonates: Synthetic Methods and Their Biological Applications - Kaboudin, Babak; Daliri, Payam; Faghih, Samaneh; Esfandiari, Hesam (Frontiers in Chemistry, 2022)
Phosphonates and bisphosphonates are stable analogs of phosphates and pyrophosphates that are characterized by one and two carbon-phosphorus bonds respectively. Among the various phosphonates and bisphosphonates, hydroxy and amino substitutes are of interest as effective in medicinal and industrial chemistry. For example, hydroxy bisphosphonates have proven to be an effective for the prevention of bone loss, especially in osteoporotic disease. On the other hand, different substitutions on the carbon atom connected to phosphorus have led to the synthesis of many different hydroxy- and amino-phosphonates and bisphosphonates, each with its distinct physical, chemical, biological, therapeutic and toxicological characteristics. Dialkyl or aryl esters of phosphonate and bisphosphonate compounds undergo hydrolysis process readily and gave valuable materials with wide applications in pharmaceutical and agricultural. This review aims to demonstrate the ongoing in the preparation of various classes of hydroxy- and amino-phosphonates and bisphosphonates. Furthermore, the current review summarizes and comprehensively describes manuscripts on biological application of hydroxyl- and amino-phosphonates and bisphosphonates since 2015 until today.